Gold-nanoparticle/copolymer-modified screen printed carbon based electrode nonenzymatic electrochemical sensor for sensitive detection of pyocyanin as a Pseudomonas aeruginosa infections biomarker - Aykol, Sevval Maral Ozcan; Kocyigit, Nilufer; Davsand, Larasu Tuana; Yagci, Ozlem; Arvasg, Melih Besir (ELSEVIER, 2026)
Pseudomonas aeruginosa causes severe infections such as wound, respiratory, and urinary tract infections. Pyocyanin, a redox-active molecule secreted by this bacterium, plays a key role in its pathogenicity and can serve as a biomarker for early infection diagnosis. In this study, we developed an electrochemical sensor exploiting the redox activity of pyocyanin for its sensitive detection. In this context, firstly, the surface printed electrode Poly (Aniline-co-Pyrrole)/Au-NP/SPCE electrode was obtained by coating gold nanoparticles onto the electrode produced by the electrocopolymerization of pyrrole and aniline together by the chronoamperometric method. A biosensor was designed to detect pyocyanin molecule in phosphate buffer solution (pH 7.4) solution using the prepared Poly(Aniline-co-Pyrrole)/Au-NP/SPCE electrode. The electrochemical performance of the hybrid electrode was evaluated using cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy analyses. The structural and morphological properties of the prepared electrode were investigated using Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction and Raman analyses. A stable electrochemical biosensor was developed for rapid and sensitive detection of pyocyanin in phosphate buffer (pH 7.4). The sensor exhibited a linear response between 0.5 mu M and 250 mu M with a detection limit of 101.88 nM and a quantification limit of 339.59 nM. The repeatability test of the sensor electrode was performed, and the relative standard deviation value was found to be 5.14 %. A Bacterial culture containing the pyocyanin molecule was used to test the biosensor's applicability in a real sample. The results of the study demonstrate the potential use of electrochemical biosensors in the diagnosis of P. aeruginosa infections. Furthermore, this study is expected to shed light on future studies using clinical patient samples (blood, saliva, etc.).
Keywords: Electrochemical biosensors; Electrochemical copolymerization; Gold nanoparticles; Pseudomonas aeruginosa; Pyocyanin; Biomarker; GRAPHENE; Chemistry